2008
DOI: 10.1038/sj.bjc.6604777
|View full text |Cite
|
Sign up to set email alerts
|

MAL promoter hypermethylation as a novel prognostic marker in gastric cancer

Abstract: T-lymphocyte maturation associated protein, MAL, has been described as a tumour-suppressor gene with diagnostic value in colorectal and oesophageal cancers, and can be inactivated by promoter hypermethylation. The aim of this study was to analyse the prevalence of MAL promoter hypermethylation and the association with mRNA expression in gastric cancers and to correlate methylation status to clinicopathological data. Bisulphite-treated DNA isolated from formalin-fixed and paraffin-embedded samples of 202 gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 26 publications
(32 reference statements)
2
50
1
Order By: Relevance
“…These findings agree with predictions made in our previous study (Figure 2a). To date, several studies have reported MAL gene methylation and mRNA-expression patterns in various cancers such as oral, breast, colon, and GC (Lind et al, 2008, Pal et al, 2012, Horne et al, 2009, Buffart et al, 2008. Buffart et al found an association between mRNA-expression levels and the methylation status of the MAL promoter region (Buffart et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…These findings agree with predictions made in our previous study (Figure 2a). To date, several studies have reported MAL gene methylation and mRNA-expression patterns in various cancers such as oral, breast, colon, and GC (Lind et al, 2008, Pal et al, 2012, Horne et al, 2009, Buffart et al, 2008. Buffart et al found an association between mRNA-expression levels and the methylation status of the MAL promoter region (Buffart et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Gene silencing by promoter hypermethylation has been described in gastric cancer for multiple genes, including CDH1, which is involved in cell adhesion, and hMLH1, which is associated with DNA mismatch repair and the cell cycle regulator p16 [8][9][10]. In addition, promoter hypermethylation of MAL has been shown to be an independent prognostic marker for gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, two regions within the MAL promoter were analyzed for methylation in gastric cancer samples. Hypermethylation of both regions occurred in 71% and 80%, respectively; however, only methylation at the region closest to the TSS was correlated with a better disease-free survival (31). In addition, increased expression of MAL in serous ovarian cancer patients with a poor prognosis is associated with decreased methylation of a specific region of the MAL promoter (40).…”
Section: Location Of Biologically Relevant Methylation In Promoter Cpmentioning
confidence: 99%